PERAN PERMAINAN OLAHRAGA TRADISIONAL HADANG TERHADAP TINGKAT KEBUGARAN JASMANI SISWA - Lingling, Lingling Usli Wargadinata (Universitas Negeri Jakarta, 2019)
The main objective of the PON West Java Football Team Training Program is to form a strong and good West Java football team, hoping to create quality players for the needs of the West Java and national football teams. This research is a program evaluation study using the CIPP model which is seen from two dimensions, namely the dimensions of interaction and input. Three dimensions, namely: 1) objectives, 2) legal basis, 3) needs analysis. Dimensions include five things, namely; 1) approve the program plan, 2) discuss human resources, 3) support the organizing organization, 4) approve the facilities and infrastructure, 5) support the funds. This research produces findings; based on the dimension of context, it is in accordance with the suitability of the objectives of the training program with the vision and mission; already has a strong legal basis and in accordance with the suitability between the Exercise program and needs analysis, based on input, already equipped with program planning documents and program guidelines, it still needs to be improved; In accordance with the suitability between the profile and the process of recruiting athletes and coaches with the specified criteria, there is good support from Assprov and KONI West Java, lack of adequate support facilities and infrastructure, and have received adequate funding. The results of this study discuss several things, namely; 1) Adjusting the suitability of the program objectives with the vision and mission, 2) Adjusting the legal program, 3) Arranging the program plan and managing the program in accordance with the needs of the program.